EFFECT OF DECOUPLED PAYMENTS ON U.S. AGRICULTURAL PRODUCTION - 김태훈 (한국농촌경제연구원, 2008)
In the current WTO negotiations, the developing and the developed countries take opposite view regarding the criteria for green box subsidies supposed to be decoupled from current production levels and prices. This study investigates whether U.S. PFC and direct payment subsidies are truly decoupled from production or not by modeling the farmers' risk attitudes in a non-structural approach and estimating the effect of decoupled payments on production by the change in risk attitudes. The effect of decoupled payments is not only statistically insignificant on corn and soybean acreage but also very small in magnitude.
Keywords: Decoupled payments; PFC payments; risk attitude; nonstructural approach; Decoupled payments; PFC payments; risk attitude; nonstructural approach